2010
DOI: 10.1099/mic.0.034363-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of UdgB and Ung in mutation prevention and protection against commonly encountered DNA damaging agents in Mycobacterium smegmatis

Abstract: The incorporation of dUMP during replication or the deamination of cytosine in DNA results in the occurrence of uracils in genomes. To maintain genomic integrity, uracil DNA glycosylases (UDGs) excise uracil from DNA and initiate the base-excision repair pathway. Here, we cloned, purified and biochemically characterized a family 5 UDG, UdgB, from Mycobacterium smegmatis to allow us to use it as a model organism to investigate the physiological significance of the novel enzyme. Studies with knockout strains sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…Because this growth defect precluded the use of fluctuation analysis to measure the mutation rate, we instead performed mutant accumulation assays and enumerated accumulation of mutations using whole genome sequencing. In a mutant accumulation assay, we found the basal mutation rate for M. smegmatis complemented with wild-type dnaE1 to be ~4.5×10 −10 mutations per base pair per generation, consistent with data from fluctuation analysis and previously published estimates ( Table 1 , Supplemental Figure 6 ) 13 . In contrast, the mutation rate in the absence of PHP exonuclease activity was ~1.0 to 1.7×10 −6 mutations per base pair per generation or ~7 to 11 mutations per genome per generation, a ~2,300–3,700 fold increase over the wild-type rate ( Table 1 ).…”
supporting
confidence: 90%
“…Because this growth defect precluded the use of fluctuation analysis to measure the mutation rate, we instead performed mutant accumulation assays and enumerated accumulation of mutations using whole genome sequencing. In a mutant accumulation assay, we found the basal mutation rate for M. smegmatis complemented with wild-type dnaE1 to be ~4.5×10 −10 mutations per base pair per generation, consistent with data from fluctuation analysis and previously published estimates ( Table 1 , Supplemental Figure 6 ) 13 . In contrast, the mutation rate in the absence of PHP exonuclease activity was ~1.0 to 1.7×10 −6 mutations per base pair per generation or ~7 to 11 mutations per genome per generation, a ~2,300–3,700 fold increase over the wild-type rate ( Table 1 ).…”
supporting
confidence: 90%
“…Interestingly, Mycobacteria have evolved remarkable redundancy in their BER system. For example, M. tuberculosis harbours two MutM homologues responsible for excision of 8-oxo-guanin [9] and also two uracil DNA glycosylases [10]. Both MutM and uracil DNAglycosylases are important in oxidative stress response.…”
Section: Introductionmentioning
confidence: 99%
“…M. smegmatis UdgB (MSMEG_5031) was amplified by PCR and subcloned into pMV261 to generate pMV261udgB, which was then introduced into an M. smegmatis rpoB : : 6 mutant by electroporation to generate a complemented strain (Malshetty et al, 2010).…”
mentioning
confidence: 99%
“…However, it should be mentioned that while the H442Y mutation and the rpoBD10 mutation in rpoB occurred in the wild-type parent strain background, the rpoB : : 6 mutation was obtained in an udgB-deficient background. Although, we have shown that UdgB deficiency does not result in any growth defects (Malshetty et al, 2010), to ensure that udgB and the rpoB : : 6 mutation together did not result in any synthetic effects we complemented the rpoB : : 6 strain with a plasmid copy of the udgB gene to generate rpoB : : 6pMV261udgB strain ( Table 1). As shown in Fig.…”
mentioning
confidence: 99%